The impact of effectuation on the performance of South African medium and high technology firms - Mthanti, Thanti Sibonelo (My University, 2013)
South Africa is blighted by high levels of unemployment and poverty. Entrepreneurship and particularly technology entrepreneurship has been seen as a possible solution to generate innovation, grow the economy and create jobs, thus reducing poverty. However, the country has struggled to commercialise its research output. This research sought to empirically test the effectiveness of the non-predictive strategy, effectuation, in improving technology commercialisation amongst South African firms. Effectuation was considered as a moderator of the EO-performance relationship amongst firms. Further, the research also tackled a research gap by exploring relationships between effectuation and established entrepreneurship and management theories such as EO and environmental hostility. Questionnaires were distributed to South African companies via email containing the web link to the survey on Qualtrics. Of the 500 emails sent, 94 companies responded with usable responses. Multiple regression analysis was used as the main statistical tool to test the hypotheses. The main findings of this study are that, for entrepreneurial high and medium technology companies, EO and environmental hostility positively predict effectuation. Further, effectuation positively moderates the relation between EO and innovative performance. The results of this study suggest entrepreneurial firms, Venture Capitalists (VCs) and government officials who wish to optimise innovative performance should revisit their emphasis on causal planning and market research.
Keywords: Entrepreneurship; Effectuation